The mediating role of quality culture on the relationship between talent management and organization performance - Abubakar, Ahmed; Abdullah, Haim Hilman (2017)
the purpose of this study was to examine the mediating role of quality culture on the relationship between talent management dimensions and organizational performance of the universities in the QS ranking.Data were collected via an online survey in which a questionnaire link was sent to 269 vice chancellors/presidents of the sampled universities.This study used proportionate random sampling for sample selection. Partial Least Squares (PLS) algorithm and bootstrap techniques were used to test the hypotheses of the study.The result revealed that talent management dimensions and quality culture had a significant positive effect on university performance.Also, the results reveal that quality culture mediated the relationship between talent retention, talent development, and performance, but it did not mediate the relationship between talent attraction and performance of universities in QS ranking. Based on the empirical evidence, talent management and quality culture were essential to university performance; therefore, universities should develop and integrate talent and quality culture for better performance.Improved university performance can address the problem of low-quality universities and place them on top university ranking.